2016
DOI: 10.3389/fimmu.2016.00642
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Intravital Imaging of the Retina Reveals Long-term Dynamics of Immune Infiltration and Its Effects on the Glial Network in Experimental Autoimmune Uveoretinitis, without Evident Signs of Neuronal Dysfunction in the Ganglion Cell Layer

Abstract: A hallmark of autoimmune retinal inflammation is the infiltration of the retina with cells of the innate and adaptive immune system, leading to detachment of the retinal layers and even to complete loss of the retinal photoreceptor layer. As the only optical system in the organism, the eye enables non-invasive longitudinal imaging studies of these local autoimmune processes and of their effects on the target tissue. Moreover, as a window to the central nervous system (CNS), the eye also reflects general neuroi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Whereas the OCT signal highlighted several retinal layers, 2PM allowed us to retrieve the localization of CX 3 CR1 + cells, presumably tissue‐resident microglia based on their GFP fluorescence. These cells play a crucial role in the disease development in the chronically inflamed central nervous system , in general, and chronically inflamed retina , in particular, as shown by us and by others.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Whereas the OCT signal highlighted several retinal layers, 2PM allowed us to retrieve the localization of CX 3 CR1 + cells, presumably tissue‐resident microglia based on their GFP fluorescence. These cells play a crucial role in the disease development in the chronically inflamed central nervous system , in general, and chronically inflamed retina , in particular, as shown by us and by others.…”
Section: Resultssupporting
confidence: 53%
“…Due to the nonlinear excitation of femtosecond pulsed lasers, the illumination in 2PM affects only a thin layer of tissue located at the focal plane. By controlling the laser power in the range of few tens of milliwatts, photodamage is typically reduced to a negligible level for mammalian tissues . Based on elastic reflection and interference, OCT typically employs low coherence light sources at extremely low powers (in the range of microwatts) .…”
mentioning
confidence: 99%
“…No rapid alterations were seen during imaging sessions, potential cell labelling could only be identified in post-processing and the expected speed of migration within retinal tissue remains unknown. Evidence from 2-photon imaging of the inflamed mouse eye however demonstrates myeloid cell movement may be much slower than expected, even compared to other tissues, at around 1 µm per minute (20). This could explain the larger time intervals required to observe signal position shifts that could represent labelled immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, IVM demonstrated that fluorescently labelled bisphosphonates, which have been shown to possess anti-tumour activity, were taken up by tumour-associated macrophages (TAMs), potentially corrupting their tumourpromoting functions (Junankar et al, 2015). Here IVM identified Imaging of fibrillar collagen in tissues including muscle, skin and tumours (Brown et al, 2003;Campagnola et al, 2002;Koenig and Riemann, 2003;Kular et al, 2015;Plotnikov et al, 2006;Zipfel et al, 2003) Imaging of fibrillar collagen in human breast tissue in relation to mammographic density (Huo et al, 2015), during cancer cell invasion (Andrlová et al, 2017) or anti-cancer drug targeting of the stromal ECM (Chang et al, 2017;Miller et al, 2015;Vennin et al, 2017) Third harmonic generation (THG) Excitation primarily occurs at water-lipid and water-protein interfaces, to provide structural information (e.g. cell morphology and surrounding ECM).…”
Section: Ivm Of the Tumour-associated Immune Systemmentioning
confidence: 97%
“…For example, live cell imaging in the retina was recently performed to observe dynamic radial infiltration patterns of immune cells in a mouse model of autoimmune retinal inflammation (Bremer et al, 2016). The auricular skin of the ear provides another easily accessible site to extract valuable in vivo cell biology without the need for surgical intervention.…”
Section: Introductionmentioning
confidence: 99%